Instant Apache Hive essentials how-to : leverage your knowledge of SQL to easily write distributed data processing applications on Hadoop using Apache Hive /: leverage your knowledge of SQL to easily write distributed data processing applications on Hadoop using Apache Hive. (2013) - Unknown
No abstract available